Enceladus and the icy moons of Saturn - Schenk, Paul M.; Clark, Roger N. (Roger Nelson); Verbiscer, Anne J.; Howett, Carly J. A.; Waite, J. H. (John H.); Dotson, Renée (Space science series., 2018)
Enceladus and the Icy Moons of Saturn brings together nearly eighty of the world's top experts to establish what we currently understand about Saturn's moons, while building the framework for the highest-priority questions to be addressed through ongoing spacecraft exploration--Provided by publisher.